2003
DOI: 10.1086/502186
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Alcohol-Based Hand Rub and Quality Improvement Interventions to Improve Hand Hygiene in a Russian Neonatal Intensive Care Unit

Abstract: HH may have increased slightly, but the largest effect was a switch from soap and water to alcohol which may have been associated with decreased cross-transmission of Klebsiella, although this may have been confounded by lower device use. Alcohol-based antiseptic may be an improvement over current practices, but further research is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 57 publications
3
53
0
1
Order By: Relevance
“…Compliance with hand hygiene recommendations by healthcare workers (HCWs) is generally disturbingly low (ie, 20%-40%), 1 " 6 with few studies reporting adherence rates greater than 50%. 7 Significant differences in compliance have been observed between the various HCW professions, with higher rates of adherence reported among nurses, particularly in those in pediatric and intensive care units. 5 Glove use, recommended in case of contact with biological fluids, has been shown to modify hand hygiene compliance and perception, 8 although data regarding glove use in relation to hand hygiene are limited.…”
mentioning
confidence: 99%
“…Compliance with hand hygiene recommendations by healthcare workers (HCWs) is generally disturbingly low (ie, 20%-40%), 1 " 6 with few studies reporting adherence rates greater than 50%. 7 Significant differences in compliance have been observed between the various HCW professions, with higher rates of adherence reported among nurses, particularly in those in pediatric and intensive care units. 5 Glove use, recommended in case of contact with biological fluids, has been shown to modify hand hygiene compliance and perception, 8 although data regarding glove use in relation to hand hygiene are limited.…”
mentioning
confidence: 99%
“…60,140,215,216,334,335,485,486,492,493,496,497,613,633,637,[648][649][650][651]654,655,657, It should be pointed out that the methods for defining adherence (or non-adherence) and the methods for conducting observations varied considerably in the reported studies, and many articles did not include detailed information about the methods and criteria used. Some studies assessed compliance with hand hygiene concerning the same patient, 60,334,648,652,666,667,683,[685][686][687] and an increasing number have recently evaluated hand hygiene compliance after contact with the patient environment. A number of investigators reported improved adherence after implementing various interventions, but most studies had short follow-up periods and did not establish if improvements were of long duration.…”
Section: Observed Adherence To Hand Cleansingmentioning
confidence: 99%
“…60,217,334,429,485,486,613,648,651,663,666,667,670,680,682,684,686,687,713,714,803,804,851,852 Recent studies have further enriched the scientific literature. 140,428,493,494,655,657,694,698,699,701,705,[707][708][709][710][715][716][717][718]728,853 In general, most studies differed greatly in their duration and intervention approach.…”
Section: Elements Of Promotion Strategiesmentioning
confidence: 99%
See 2 more Smart Citations